Evasion of toll-like receptor recognition by Escherichia coli is mediated via population level regulation of flagellin production - Tan, Aaron; Alsenani, Qusai; Lanz, Marcello; Birchall, Christopher; Drage, Lauren K. L.; Picton, David; Mowbray, Catherine; Ali, Ased; Harding, Christopher; Pickard, Robert S.; Hall, Judith; Aldridge, Phillip D. (Frontiers in Microbiology, 2023)
Uropathogenic Escherichia coli is a major cause of urinary tract infections. Analysis of the innate immune response in immortalised urothelial cells suggests that the bacterial flagellar subunit, flagellin, is key in inducing host defences. A panel of 48 clinical uro-associated E. coli isolates recovered from either cystitis, pyelonephritis asymptomatic bacteriuria (ABU) or UTI-associated bacteraemia infections were characterised for motility and their ability to induce an innate response in urothelial cells stably transfected with a NFκB luciferase reporter. Thirty-two isolates (67%) were identified as motile with strains recovered from cystitis patients exhibiting an uneven motility distribution pattern; seven of the cystitis isolates were associated with a > 5-fold increase in NFκB signalling. To explore whether the NFκB signalling response reflected antigenic variation, flagellin was purified from 14 different isolates. Purified flagellin filaments generated comparable NFκB signalling responses, irrespective of either the source of the isolate or H-serotype. These data argued against any variability between isolates being related to flagellin itself. Investigations also argued that neither TLR4 dependent recognition of bacterial lipopolysaccharide nor growth fitness of the isolates played key roles in leading to the variable host response. To determine the roles, if any, of flagellar abundance in inducing these variable responses, flagellar hook numbers of a range of cystitis and ABU isolates were quantified. Images suggested that up to 60% of the isolate population exhibited flagella with the numbers averaging between 1 and 2 flagella per bacterial cell. These data suggest that selective pressures exist in the urinary tract that allow uro-associated E. coli strains to maintain motility, but exploit population heterogeneity, which together function to prevent host TLR5 recognition and bacterial killing.